A difusão do autoritarismo e resistência constitucional - Ferreira, Emanuel de Melo (2022)
The inclusive, social, and democratic nature of the Brazilian Federal Constitution of 1988 has been targeted by an erosion process, which aims to suppress its normativity. This phenomenon, to the extent that it seeks, in various ways, to praise the military dictatorship, can be described as an authoritarian project developing as a struggle against democratic institutions. This thesis aims to demonstrate how those practices has been disseminated throughout the institutions, which are working in a collaborative and authoritarian way, systematizing how such practices have been disseminated throughout the Brazilian state and what their consequences are for a variety of social groups. These groups, despite being victims of authoritarianism, also attempt to oppose its advances, pursuing forms of constitutional resistance. In this scenario, the main question of the thesis is: what are the characteristics of the mentioned diffuse unconstitutional practices verified in Brazil? Answering this question requires the systematization of the various non-democratic manifestations observed in the country and their relationship with law. More specifically, the focus is on practices which develop from the military dictatorship’s legacies and are aimed at disseminating fear amongst those viewed as “enemies”: a) praise of the military dictatorship within the scope of obstacles to Transitional Justice measures; b) acts of disobedience by the military police; c) diverse intimidation techniques. The hypothesis to be tested is that authoritarianism has developed only because ordinary judges and the Public Prosecutor’s Offices dialogues in a coordinated way in a context of anti-democratic principles of political governance. To achieve acceptable answers, the present research uses case study methodology, focusing on diffuse judicial review of constitutional matters. Such processes are considered more appropriate to investigate how antidemocratic practices disseminate beyond the holophotes normally directed to Brazil’s Supreme Court and its acts of concentrated judicial review. The study analyzes several class actions, criminal complaints, legal opinions, judicial decisions, legal reports, civil investigations, and case fillings from Brazilian judicial and prosecutorial institutions. Documents were accessed through the respective institutional databases and selected to the extent that they contained manifestations of one of the three authoritarian legacies described earlier. The research concludes that the diffusion of authoritarianism occurs through interinstitutional interactions constituting a coordinated conversation between various officials engaged in developing antidemocratic practices. This phenomenon is only possible because there is a relevant omission of the State in what concerns the protection of democracy. The thesis’ departing hypothesis is, therefore, partially verified: although focuses of constitutional resistance exist in various institutions and social groups, the referred authoritarian legacies manage to impose themselves. In this process, the lenience of some federal judges and federal prosecutors proves especially relevant. The thesis sustains that there is a diffuse collaborationism throughout officials, specially judges and prosecution officers, against 1988’s constitutional project, being that conduct decisive for the perpetuation of the authoritarian legacies.